Platform Capitalism (excerpts) - Nick Srnicek; Maria Dobryakova (Journal of Economic Sociology, 2019)
This book discusses the transformation of firms into platforms—companies providing software and hardware products to others—that has occurred in many economic sectors. This massive transformation resulted from switching capitalism into data, considering them as a source for economic growth and resilience. Changes in digital technologies contributed much to the relationships between companies and their workers, clients, and other capitalists, who increasingly began to rely on data. Dr. Nick Srnicek critically reviews “platform capitalism”, putting new forms of the business model into the context of economic history, tracing their evolution from the long downturn of the 1970s to the economic boom of the 1990s and to the consequences of the 2008 financial crisis. The author demonstrates that the global economy was re-divided among a few of the monopolistic platforms and shows how these platforms set up new internal trends for the development of capitalism.The Journal of Economic Sociology further publishes some excerpts from the second chapter, which is named “Platform Capitalism” after the title of the book. This chapter is an attempt to provide clarity to various ongoing discussions in the new world, as it lays out a typology (i.e., cloud platforms, advertising platforms, lean platforms, industrial platforms, and product platforms) and the genesis of platforms.